EXTENDING ONLINE AND BLENDED LEARNING TO CORPORATIONS IN THE NEW YORK METROPOLITAN REGION - Ubell, Robert (Online Learning, 2007)
WebCampus.Stevens, the online graduate education and corporate training unit of Stevens Institute of Technology, delivers one of the largest and most effective ALN and blended programs of any college or university in the New York metropolitan region. Under a newly awarded Sloan Foundation grant [1], the school is extending its engineering and management programs to area corporations, supporting local telecommunications, pharmaceutical/life sciences, media, finance and other key industries. Stevens provides local employees of Fortune 500 and other companies access to high-quality online advanced technical and managerial skills, preparing them for success in global competition. Established in 1870, Stevens offers baccalaureate, masters and doctoral degrees in engineering, science, computer science, management and technology management, as well as a baccalaureate in the humanities and liberal arts, and in business and technology. The university enrolls about 1,800 undergraduates and 2,600 graduate students. It is one of the oldest and most respected engineering and management schools in the nation with a long tradition of meeting the technical and managerial needs of local industry.